2018
DOI: 10.1159/000489464
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Head and Neck Surgery: History, Technical Evolution and the Future

Abstract: The first application of robotic technology in surgery was described in 1985 when a robot was used to define the trajectory for a stereotactic brain biopsy. Following its successful application in a variety of surgical operations, the da Vinci® robot, the most widely used surgical robot at present, made its clinical debut in otorhinolaryngology and head and neck surgery in 2005 when the first transoral robotic surgery (TORS) resections of base of tongue neoplasms were reported. Subsequently, the indications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
0
27
0
3
Order By: Relevance
“…Robotic surgery was first used in 1985 (11). The first application of robotic surgery in head and neck cancer occurred 20 years later in 2005 when McLeod and Melder used the da Vinci robot to resect a vallecular cyst (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robotic surgery was first used in 1985 (11). The first application of robotic surgery in head and neck cancer occurred 20 years later in 2005 when McLeod and Melder used the da Vinci robot to resect a vallecular cyst (12).…”
Section: Methodsmentioning
confidence: 99%
“…That same study concluded that TORS is currently underutilized due to the associated expenses (59), particularly in countries with limited resources such as Estonia, Latvia, and Lithuania where TORS is currently unavailable. Although cost is currently an important barrier to the wider uptake of robotic surgery, the impending commercialization of new, smaller, more flexible surgical robots is likely to decrease costs, and expand current indications for TORS (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that with updates of CT and MRI equipment, thinner layers and newer pixel technologies will continue to emerge, and image-mediated clinical surgery will be more accurate and have a greater clinical value. Just as Garas and Arora [15] said, future directions relate to overlay technology through augmented reality that allows real-time image guidance.…”
Section: Discussionmentioning
confidence: 99%
“…TORS using the da Vinci also provides the surgeon with a three-dimensional view and endo-wristed instruments with seven degrees of freedom, thereby ameliorating surgical dexterity. 7 In contrast to trans-oral LASER microsurgery (TLM), where line-of-sight can be a significant issue, tumors can be resected en-bloc using TORS, maintaining the essential surgical oncology principle not to remove the tumor piecemeal. This also permits better histopathological assessment of the tumor; of great importance when considering treatment de-escalation.…”
Section: A Brief History Of Robotic Surgery In Entmentioning
confidence: 99%